The Use of MOOCS in Developing Children's Dance Choreography Through the Stages of Inspiration, Percolation, Preparation, Creation, and Reflection - Wida Rahayuningtyas; Mohamad Fitri Bin Mohamad Haris; Ika Wahyu Widyawati; Winda Istiandini; Surasak Jamnongsarn (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study investigates the application of Massive Open Online Courses (MOOCs) in children's dance education through the Inspiration, Percolation, Preparation, Creation, and Reflection (IPPCR) framework. The primary objective is to design a MOOC that enhances students' motor skills and creativity while simultaneously improving accessibility to dance education. The research employs a development approach using the ADDIE model. The implementation of the MOOC produced choreography materials for children's dance, which include choreographic sequences, movement compositions, various categories of movement design, and floor patterns. In the first stage, Inspiration, students are encouraged to seek ideas from diverse sources, including visual, auditory, and life experiences. The second stage, Percolation, allows students to reflect on and internalize the collected ideas, giving them time to mature organically without external pressure. The third stage, Preparation, involves planning, during which students organize the steps and techniques required for their artistic projects. In the fourth stage, Creation, students bring their artistic works to realization. The final stage, Reflection, engages students in evaluating both the outcomes of their work and the creative processes they have undertaken